Did anomalous atmospheric circulation favor the spread of COVID-19 in Europe? - Sanchez Lorenzo, A.; Vaquero Martínez, J.; Calbó, J.; Wild, M.; Santurtún Zarrabeitia, Ana; Lopez Bustins, J.A.; Vaquero, J.M.; Folini, D.; Antón, M. (Environmental Research, 2021)
The current pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is having negative health, social and economic consequences worldwide. In Europe, the pandemic started to develop strongly at the end of February and beginning of March 2020. Subsequently, it spread over the continent, with special virulence in northern Italy and inland Spain. In this study we show that an unusual persistent anticyclonic situation prevailing in southwestern Europe during February 2020 (i.e. anomalously strong positive phase of the North Atlantic and Arctic Oscillations) could have resulted in favorable conditions, e.g., in terms of air temperature and humidity among other factors, in Italy and Spain for a quicker spread of the virus compared with the rest of the European countries. It seems plausible that the strong atmospheric stability and associated dry conditions that dominated in these regions may have favored the virus propagation, both outdoors and especially indoors, by short-range droplet and aerosol (airborne) transmission, or/and by changing social contact patterns. Later recent atmospheric circulation conditions in Europe (July 2020) and the U.S. (October 2020) seem to support our hypothesis, although further research is needed in order to evaluate other confounding variables. Interestingly, the atmospheric conditions during the Spanish flu pandemic in 1918 seem to have resembled at some stage with the current COVID-19 pandemic. A, Sanchez-Lorenzo was supported by a fellowship (RYC-2016–20784) and a project (PID2019-105901RB-I00) funded by the Ministry of Science and Innovation of Spain. Javier Vaquero-Martinez was supported by a predoctoral fellowship (PD18029) from Junta de Extremadura and European Social Fund. J.A. Lopez-Bustins was supported by Climatology Group of the University of Barcelona (2017 SGR 1362, Catalan Government) and the CLICES project (CGL2017-83866-C3-2-R, AEI/FEDER, UE). This research was supported by the Economy and ...